Saccadic eye movement applications for psychiatric disorders - Bittencourt J (Dove Medical Press, 2013)
Juliana Bittencourt,1–4 Bruna Velasques,1–3,5 Silmar Teixeira,1,2,4 Luis F Basile,6,7 José Inácio Salles,5,8 Antonio Egídio Nardi,9 Henning Budde,10 Mauricio Cagy,11 Roberto Piedade,1 Pedro Ribeiro1,2,12 1Brain Mapping and Sensory Motor Integration Laboratory, Institute of Psychiatry, Federal University of Rio de Janeiro, 2Institute of Applied Neuroscience, Rio de Janeiro, 3Neurophysiology and Neuropsychology of Attention, Institute of Psychiatry, Federal University of Rio de Janeiro, Rio de Janeiro, 4Laboratory of Physical Therapy, Veiga de Almeida University, Rio de Janeiro, 5Neuromuscular Research Laboratory, National Institute of Traumatology and Orthopaedics, Rio de Janeiro, 6Division of Neurosurgery, University of São Paulo Medical School, São Paulo, 7Laboratory of Psychophysiology, Department of Psychology and Phonoaudiology, Universidade Metodista do Estado de São Paulo (UMESP), São Paulo, 8Brazilian Volleyball Confederation, Rio de Janeiro, 9Panic and Respiration Laboratory, Federal University of Rio de Janeiro, Instituto Nacional de Ciência e Tecnologia (INCT) e Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), Rio de Janeiro, Brazil; 10Department of Sport Science and Physical Education, School of Science and Engineering, Reykjavik University, Reykjavik, Iceland; 11Biomedical Engineering Program, Coordenação dos Programas de Pós-Graduação em Engenharia (COPPE), Federal University of Rio de Janeiro, Rio de Janeiro; 12School of Physical Education, Bioscience Department Escola de Educação Física e Desportos da Universidade Federal do Rio de Janeiro (EEFD/UFRJ), Rio de Janeiro, Brazil Objective: The study presented here analyzed the patterns of relationship between oculomotor performance and psychopathology, focusing on depression, bipolar disorder, schizophrenia, attention-deficit hyperactivity disorder, and anxiety disorder. Methods: Scientific articles published from 1967 to 2013 in the PubMed/Medline, ISI Web of Knowledge, Cochrane, and SciELO databases were reviewed. Results: Saccadic eye movement appears to be heavily involved in psychiatric diseases covered in this review via a direct mechanism. The changes seen in the execution of eye movement tasks in patients with psychopathologies of various studies confirm that eye movement is associated with the cognitive and motor system. Conclusion: Saccadic eye movement changes appear to be heavily involved in the psychiatric disorders covered in this review and may be considered a possible marker of some disorders. The few existing studies that approach the topic demonstrate a need to improve the experimental paradigms, as well as the methods of analysis. Most of them report behavioral variables (latency/reaction time), though electrophysiological measures are absent. Keywords: depression, bipolar disorder, attention-deficit hyperactivity disorder, schizophrenia, anxiety disorder